Development of an innovative macroalgae biorefinery: Oligosaccharides as pivotal compounds. (15th July 2022) - Andrade, Cristiana; Martins, Pedro L.; Duarte, Luís C.; Oliveira, Ana Cristina; Carvalheiro, Florbela
Graphical abstract: Highlights: U. lactuca is rich in polysaccharides with a high diversity of sugar constituents. All of the four tested processes can effectively produced oligosaccharides (OS) Optimal OS production conditions are milder than the required for land plants. Dilute acid hydrolysis presented high selectivity and higher oligosaccharides yield. All pre-treatment processes produce biomass enriched in glucan and protein. Abstract: Macroalgae have significant advantages over land-living biomass resources and are promising pivotal feedstocks for the onset of the blue bioeconomy. Among these, Ulva lactuca has demonstrated a high potential due to its wide distribution and high productivity. In this work, a detailed chemical characterization of U. lactuca enabled the identification of polysaccharides as the main macromolecular component of the organic fraction. They present a high diversity of sugar constituents and hence can be a relevant source of added-value oligosaccharides for the food/feed industries. Four processes, with increasing operational temperatures, were compared for the selective production of oligosaccharides: Conventional Soxhlet Extraction, Accelerated Solvent Extraction, Hydrothermal treatment (HT) and Dilute Acid Hydrolysis (DAH). All processes presented high oligosaccharide/monosaccharide ratios, with HT and DAH exhibiting the highest oligosaccharides yields (10.6 and 16.6 g/100 g initial biomass, respectively). These oligosaccharides were obtained under milder, more economic conditions than the reported for lignocellulosic (land) plants and can represent an important added-value income of the algae biorefineries and thus contribute to their economic sustainability.